Limosilactobacillus reuteri 29a cell-free supernatant antibiofilm and antagonistic effects in murine model of vulvovaginal candidiasis - Boahen, Angela; Chew, Shu Yih; Neela, Vasantha Kumari; Than, Leslie Thian Lung (Springer, 2023)
Vaginal dysbiosis advocates burgeoning of devious human vaginal pathobionts like Candida species that possess multiple virulence properties and metabolic flexibility to cause infections. Inevitably, antifungal resistance may emerge due to their innate nature (e.g., biofilm formation), which assists in their virulence as well as the formation of persister cells after dispersal. In consequence, the phenomenon of biofilm involvement in vulvovaginal candidiasis (VVC) and its recurrence is becoming paramount. Lactic acid bacteria and their derivatives have proven to be hostile to Candida species. Here, we throw more light on the potency of the derivatives, i.e., cell-free supernatant (CFS) produced by an indigenously isolated vaginal Lactobacillus strain, Limosilactobacillus reuteri 29A. In the present study, we investigated the antibiofilm and antagonistic effects of L. reuteri 29A CFS, against biofilms of Candida species and in murine model of vulvovaginal candidiasis. In our in vitro biofilm study, the CFS disrupted and inhibited preformed biofilms of C. albicans and C. glabrata. Scanning electron microscopy displayed the destruction of preformed biofilms and impediment of C. albicans morphogenesis by the CFS. Gas chromatography–mass spectrometry analysis showed multiple key compounds that may act singly or synergistically. In vivo, the CFS showed no collateral damage to uninfected mice; the integrity of infected vaginal tissues was restored by the administration of the CFS as seen from the cytological, histopathological, and electron microscopical analyses. The results of this study document the potential use of CFS as an adjuvant or prophylactic option in addressing vaginal fungal infections.